Korosifitas air terhadap fondasi beton, kasus di daerah Tapin, Kalimantan - Matahelumual, Bethy Carolina (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no2.20071Corrosion means damaged metal or rust and it could cause explosion in industrial boiler, broken pipe, or stucked gun. Survey result shows that corrosion does not only occur on metals but it may form on building’s concrete. Some factors enable to form corrosion are temperature, dissolved salt, and microor- ganism activity.Corrosivity is influenced by the existence of low pH (concentration of Hidrogen ion), agressive CO , ammonium (NH +), magnesium (Mg+2), and sulphate (SO -2), and pH is the main factor for being concerned of corrosivity. The corrosion may begin to form at water pH of 4.5; the lower pH of water, the faster it forms.On July 2002, the area of KUD Makmur, Tambarangan village was chosen for corrosion study of concrete. Six water samples were analyzed for identification of some chemical elements which influenced the concrete corrosion. Analysis result exhibited that the water had acid characteristics with pH of 3.8-5.1, and the main compounds were CO , NH +, Mg+2, and SO -2; showing that the water ranged of high to very high corrosion character.A special water treatment needs to do in increasing the quality of water, so that the water could be used for foundation concrete, or to prevent corrosion by coating the inner surface of pipe by carbonate. Some parameters in building of foundation should consider such as firstly on planning, followed by environment data collection, and then building process, choosing equipments and maintenance.